Syphilitic balanitis of Follmann in a patient with a history of previous infection. (June 2023) - Campoli, Marco; Cozzi, Chiara; Caravello, Simone; Minuti, Anna; Lombardo, Maurizio; Salvemini, Isabella; Zerbinati, Nicola
We report a case of syphilitic balanitis of Follmann arising in a man with a history of prior infection with syphilis. Few cases have been described in the literature. In our case, a man with history of multiple unprotected sexual contacts presented with erosive balanitis and painless inguinal bilateral lymphadenopathy. All tests for sexually transmitted infections (STIs) performed were negative with the exception of serology for syphilis. We made the diagnosis of syphilitic balanitis of Follmann that was confirmed by prompt resolution after treatment.